Relationship Between the Results of the Landing Error Scoring System and Trunk Muscle Thickness - Yuki Muramoto; Hironobu Kuruma (North American Sports Medicine Institute, 2024)
# Background A landing error scoring system (LESS) is widely used to evaluate landing maneuvers. Poor landing maneuvers, such as lateral bending of the trunk, are thought to be associated with a risk of lower-extremity injury. However, no studies have examined the association between landing and trunk muscle function, which is associated with a high risk of lower-extremity injury. # Hypothesis/Purpose This study examined whether an association exists between landing movements and a high risk of lower-extremity injury and trunk muscle function. It was hypothesized that athletes with poor activation of deep trunk muscle (transversus abdominis and internal oblique) would have lower LESS scores. # Study Design Cross-sectional study # Methods The trunk muscle thickness at rest and during the plank was measured using ultrasonography. The percent of change in muscle thickness (during plank/at rest) was calculated. The LESS was measured using the Physimax. Based on the LESS scores, patients were divided into high- (LESS > 6) and low-risk (5 > LESS) groups for lower extremity injury. The relationship between the high-risk group and trunk muscle thickness was examined using a stepwise regression analysis. # Results The high-risk group had significantly lower muscle thicknesses of the transversus abdominis (p=0.02) and transversus abdominis plus internal oblique abdominis (p=0.03) muscles during the plank. Additionally, the high-risk group showed significantly lower percent of change in muscle thickness of the internal oblique (p=0.02) and transversus abdominis plus internal oblique (p=0.01) muscles. Only the percentage of change in the thickness of the internal oblique and transverse abdominal muscles was extracted from the regression as a factor. # Conclusion The findings indicated that athletes with landing movements and a high risk of injury, as determined based on the LESS results, had low trunk muscle function, and a relationship was observed between the change in thickness of transversus abdominis and internal oblique abdominis muscles. # Level of Evidence 3B